"The Big Book of Sales Training Games: Quick, Fun Activities for Improving Selling Skills or Livering Up a Sales Meeting" - Carlaw (Peggy); Vasudha Kathleen Deming (2008)
Sales Management
22.5
Keywords: Sales Management